Design and Implementation of Blind Source Separation Based on BP Neural Network in Space-Based AIS - Li, Chengjie; Zhu, Lidong; Luo, Zhongqiang; Zhang, Zhen; Liu, Yilun; Yang, Ying (Frontiers in Space Technologies, 2021)
In space-based AIS (Automatic Identification System), due to the high orbit and wide coverage of the satellite, there are many self-organizing communities within the observation range of the satellite, and the signals will inevitably conflict, which reduces the probability of ship detection. In this paper, to improve system processing power and security, according to the characteristics of neural network that can efficiently find the optimal solution of a problem, proposes a method that combines the problem of blind source separation with BP neural network, using the generated suitable data set to train the neural network, thereby automatically generating a traditional blind signal separation algorithm with a more stable separation effect. At last, through the simulation results of combining the blind source separation problem with BP neural network, the performance and stability of the space-based AIS can be effectively improved.